2023
DOI: 10.3389/fmars.2023.1086166
|View full text |Cite
|
Sign up to set email alerts
|

Response of bacterial communities (Marivita, Marinobacter, and Oceanicaulis) in the phycosphere to the growth of Phaeodactylum tricornutum in different inorganic nitrogen sources

Abstract: IntroductionIn marine ecosystems, microbial communities are important drivers of material circulation and energy flow. The complex interactions between phytoplankton and bacterial communities constitute one of the most crucial ecological relationships in the marine environment. Inorganic nitrogen can affect the type of relationship between algae and bacteria. However, the quantitative relationship between the bacterial communities, inorganic nitrogen, and phytoplankton remains unclear.MethodsUnder laboratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In contrast to competitive interactions, Algoriphagus can form a synergistic relationship with O. borgei and promote the accumulation of chlorophyll a [40]. The genus Marinobacter has the ability to secrete ammonium nitrogen, thereby promoting algal growth and chlorophyll a synthesis [41,42]. Ling et al found that Marinobacter can promote the growth of seven microalgal species [43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to competitive interactions, Algoriphagus can form a synergistic relationship with O. borgei and promote the accumulation of chlorophyll a [40]. The genus Marinobacter has the ability to secrete ammonium nitrogen, thereby promoting algal growth and chlorophyll a synthesis [41,42]. Ling et al found that Marinobacter can promote the growth of seven microalgal species [43].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the elevated abundance of Marivita and Pseudomonas in the water at 30 and 90 days. Marivita is associated with the uptake and metabolism of carbon, nitrogen, and phosphorus inorganic or organic compounds, and its increased abundance is usually accompanied by phytoplankton outbreaks or organic-rich environments [37,38]. With the fixation of carbon and nitrogen by microorganisms and phytoplankton, the increase in residual baited feces, and the gradual accumulation of organic matter, the abundance of Marivita gradually increased.…”
Section: Analysis Of the Influence Factors Of The Gut Microorganismsmentioning
confidence: 99%